SOME QUALITY INDICATORS OF SKINS IN OFFSPRING OBTAINED FROM MATING OF BUKHARA BROWN SHEEP IN DIFFERENT VARIANTS - Bazarov Soli Rahmatovich; Yorqulov Xusan Narzullayevich (Scholar Express Journals, 2023)
The purpose of this work is to present the results of the skin thickness and strength of the black skins of the progeny obtained from the mating of the parents according to the expression of color
Keywords: Karakol sheep; Karakol skin; gray color